Sociocultural-Based Language Learning for Strengthening Communicative Competence - Amanda Yakob Alanda; Yance Lavinko; Karine Madatyan (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The increasing demands of global communication require language learners to develop communicative competence beyond grammatical mastery. Sociocultural-based language learning has emerged as an effective approach that integrates linguistic knowledge with cultural understanding, social interaction, and authentic communication practices. This study aims to examine the contribution of sociocultural-based language learning to strengthening communicative competence among foreign language learners. Employing a qualitative library research design, the study analyzed twenty-five scholarly publications published between 2010 and 2026. The findings reveal that sociocultural learning environments significantly enhance communicative competence through collaborative interaction, mediation, authentic materials, role-playing activities, service-learning projects, and intercultural engagement. Furthermore, sociocultural approaches facilitate learners' sociolinguistic awareness, cultural sensitivity, and pragmatic language use, which are essential components of communicative competence. The analysis demonstrates that communicative competence develops most effectively when language learning occurs in socially meaningful contexts where learners actively negotiate meaning and participate in authentic discourse communities. The study concludes that sociocultural-based language learning provides a comprehensive framework for improving communicative competence and should be integrated into foreign language curricula. The findings offer pedagogical implications for language educators seeking to design more interactive, culturally responsive, and communication-oriented learning environments.